“I Have a Voice—Hear Me!” Findings of an Australian Study Examining the Resettlement and Integration Experience of Refugees and Migrants from the Horn of Africa in Australia - Pittaway, Eileen; Muli, Chrisanta; Shteir, Sarah (Refuge: Canada's Journal on Refugees, 2011)
Using the lens of “integration criteria” developed by Ager and Strang, this article presents the findings of a project documenting the resettlement and integration experiences of refugees and migrants from the Horn of Africa (HoA) in Australia. While refugees have enormous potential to integrate successfully, and many do, there are obstacles which persist. These include: trauma; separation of family members; lack of adequate on-arrival information and support; difficulties with language acquisition; lack of access to appropriate and affordable housing; lack of education support; discrimination in the work force; conflict within families; racism; and violence against women.